Prostate Cancer Development Is Not Affected by Statin Use in Patients with Elevated PSA Levels - Meijer, Dennie (Cancers (Basel), 2019)
Background: The role of statins in prostate cancer (PCa) remains unclear. Conflicting evidence has been found concerning risk reduction with the use of statins on biochemical recurrence (BCR). In this study, we evaluated whether statin use decreases the incidence of advanced PCa in males with elevated prostate-specific antigen (PSA; ≥4.0 ng/mL) levels and determined whether statin use reduces the risk of BCR after radical prostatectomy (RP). Methods: Patients visiting the outpatient urology clinic of the VU Medical Center between 2006 and 2018 with elevated PSA were retrospectively analyzed. Biochemical recurrence after RP was defined as a PSA level of ≥0.2 ng/mL (measured twice). Results: A total of 1566 patients were included, of which 1122 (72%) were diagnosed with PCa. At the time of diagnosis, 252 patients (23%) used statins compared to 83 patients (19%) in the non-malignancy group (p = 0.10). No differences were found in the use of statins between the different risk groups. No correlation was found between the risk of BCR after RP and the use of statins in the total (p = 0.20), the intermediate-risk group (p = 0.63) or the high-risk group (p = 0.14). Conclusion: The use of statins does not affect PCa development/progression in patients with elevated PSA levels, nor the development of BCR after RP.